Analisis Faktor Kesuksesan Pengelolaan Desa Wisata Berkelanjutan: Studi Kasus di Jawa Barat - Purnawan, Arif Hadi; Rahmanita, Myrza (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research examines the success factors in the management of sustainable tourism villages in West Java. Methodology/approach: This study employs a Systematic Literature Review (SLR) of 32 Scopus and SSCI-indexed articles (2018–2023) with an impact factor of ?3.0, focusing on sustainable tourism villages, digital innovation, and cultural preservation. Secondary data were also obtained from Statistics Indonesia (BPS), the West Java Tourism Office, and interviews with tourism village managers. Results/findings: The success of sustainable tourism villages in West Java is driven by penta-helix collaboration, community-based monitoring, digital innovation, cultural preservation, environmental management, and the diversification of the creative economy through digital platforms. These factors are integrated and mutually support sustainable village management. Conclusions: The effective management of sustainable tourism villages in West Java is supported by penta-helix collaboration, community-based monitoring, transparent financial management, digital innovation, socio-cultural preservation, resource management, and creative economy diversification through digital platforms. These integrated factors significantly contribute to the sustainable development of tourism villages. Limitations: This study is limited to research conducted in the West Java region. Other regions remain to be explored using similar research frameworks or different approaches to sustainable tourism village management and sustainable development (SDGs). Contribution: This research is expected to contribute to the fields of tourism studies, tourism village management, and other relevant scientific disciplines.